TRANSMISSIBILITY OF Fusarium oxysporum f. sp. vasinfectum INOCULATED IN COTTONSEEDS (Nucleus, 2018)
The objective of this study was to evaluate the transmissibility of Fusarium oxysporum f.sp. vasinfectum by inoculated cottonseeds. The cottonseeds were inoculated using the water restriction technique, at different times of exposure. A completely randomized design was used in the laboratory and a randomized design with blocks was used in the field experiment, with a 2x5 factorial arrangement with two cultivars (FMT 701 and Delta Opal) and five times of exposure of the pathogen in seeds (0 h, 24 h, 48 h, 72 h and 96 h). There was a reduction in the percentage of germination with the increase of the infection of the seeds when in greater time of contact with the fungus. Delta Opal cultivar presented minor disease index and major pathogen incidence when compared to FMT 701 cultivar. The rates of infection and transmission of the seed pathogen were effective and directly proportional to the inoculum potential in the seeds, with rates of 95% and 1.2%, respectively.